Assessment of kenaf (Hibiscus cannabinus) bioretting process by locally isolated microorganisms - Muthu Kumar, Kohgilaa (2014)
Kenaf (Hibiscus cannabinus L.) is a fast growing warm seasonal plant in the family of Malvaceae cultivated mainly for its fibre. The two distinct layers in kenaf stalk include the inner core and outer bast layer. The process of removing non cellulosic substances in kenaf to obtain high quality bast fibres is retting. Common method of retting is by placing kenaf in water where microorganisms degrade the pectin rich middle lamella connecting adjacent fibre cells and release bast fibre. However, the long retting time is not economically worthy and causes pollution. The aim of the study is to assess and characterize kenaf bast fibre retted by microorganisms. Following that, microorganisms were isolated from various sources of kenaf and screened for enzyme activities. The retting capacities of these microorganisms were evaluated by treating the kenaf in the monoculture of each isolates. Total of five fungi and three bacteria isolated. These isolates were identified based on morphological structures, biochemical tests and API Kit analysis. All fungal isolates were identified to be Aspergillus sp. The bacterial isolates were identified as Bacillus sp and Sphingomonas sp. The isolates were screened for cellulase, hemicellulase and pectinase production. The enzyme activities were determined by growing the fungal isolates in solid state fermentation and bacterial isolates in submerged fermentation. Both fungal and bacterial isolates showed higher pectinase activities compared to cellulase and hemicellulase activities. Pectinase activity of fungal isolates varies between different isolates and treatment days and the activities for all the isolates increased from third day onwards. Three isolates Aspergillus sp. P1, Aspergillus sp. P2 and Aspergillus sp. M1 showed higher pectinase activity (0.03 – 0.06 μg/ml/min) compared to the other two isolates, Aspergillus sp. P3 and Aspergillus sp. M2. Highest pectinase activity of bacterial isolates recorded at 12th h which ranged between 0.04 – 0.09 μg/ml/min. Bioretting process was performed by treating kenaf stalk with monoculture of the fungal isolates for five days. The samples were then evaluated for fibre brightness and tensile strength. All the treated fibres showed brightness within the range of 65 – 75% based on CIE L.a.b system. The tensile strength recorded lies within the range of 150 – 500 MPa which varies between isolates on different treatment days. In conclusion, retting reached completion on third day of treatment producing fibres of considerable tensile strength and brightness. The fibres were also easily separated and combed upon retting. Fungal and bacterial inoculums substantially improved the kenaf retting process.